Pengaruh Kebijakan Pertanggungjawaban Akuntansi Sektor Publik dan Efektivitas Alokasi Dana Gampong (ADG) Terhadap Pembangunan Fisik - Arjuli Arjuli; Cut Delsie Hasrina; Yusri Yusri (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This aim of this research is to study the policies effect of public sector accounting accountability and the effectiveness of Alokasi Dana Gampong (ADG) on physical development in Aie Village, Simeulue. The object of this research is the ADG in Aie Village, Simeulue. This research is a descriptive research. The data used are primary data, namely data derived from interviews with village officials and the community. Secondary data is also used from this study, namely data originating from literature. The results of this research shown that the accountability of ADG reports is in accordance with the principles of public accounting, and has implemented a good transparency and accountability. In addition, the ADG of Aie Village, Simeulue was also effective eventhough the planning stage was not good enough.